2008
DOI: 10.5194/acp-8-5919-2008
|View full text |Cite
|
Sign up to set email alerts
|

Consistent simulation of bromine chemistry from the marine boundary layer to the stratosphere – Part 2: Bromocarbons

Abstract: Abstract. In this second part of a series of articles dedicated to a detailed analysis of bromine chemistry in the atmosphere we address one (out of two) dominant natural sources of reactive bromine. The two main source categories are the release of bromine from sea salt and the decomposition of bromocarbons by photolysis and reaction with OH. Here, we focus on C1-bromocarbons. We show that the atmospheric chemistry general circulation model ECHAM5/MESSy realistically simulates their emission, transport and de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
65
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 67 publications
(101 reference statements)
12
65
1
Order By: Relevance
“…This implies that the 280 Gg Br yr −1 tropical coastal emissions used in Scenario C is likely too high. This agrees with the results from Kerkweg et al (2008) who found that with emission Scenario 5 from Warwick et al (2006) (Scenario C in the study), the simulated CHBr 3 is too high compared to observations in the UT/LS.…”
Section: Impact Of Emissionsupporting
confidence: 82%
See 3 more Smart Citations
“…This implies that the 280 Gg Br yr −1 tropical coastal emissions used in Scenario C is likely too high. This agrees with the results from Kerkweg et al (2008) who found that with emission Scenario 5 from Warwick et al (2006) (Scenario C in the study), the simulated CHBr 3 is too high compared to observations in the UT/LS.…”
Section: Impact Of Emissionsupporting
confidence: 82%
“…Degradation of CH 2 Br 2 occurs predominantly via reaction with OH (τ hυ =8300 days, τ OH =143 days). The simulated atmospheric lifetime of CH 2 Br 2 is 140 days, longer than the 100 days calculated in Kerkweg et al (2008). Our simulated seasonal cycle of CHBr 3 at Hawaii (maximum in winter ∼0.7 pptv and minimum in summer ∼0.3 pptv) matches well with observations from Atlas and Ridley (1996).…”
Section: Bromine Chemistry In the Geos Ccmsupporting
confidence: 75%
See 2 more Smart Citations
“…Bromine radical chemistry in the troposphere is initiated by the production of gas-phase inorganic bromine (Br y ) from photolysis and oxidation of short-lived bromocarbons and from debromination of sea-salt aerosol (Yang et al, 2005;Kerkweg et al, 2008). Br y cycles between BrO x and nonradical reservoirs (principally HBr, HOBr, BrNO 3 , BrNO 2 , Br 2 ) and is eventually lost by deposition.…”
Section: J P Parrella Et Al: Tropospheric Bromine Chemistrymentioning
confidence: 99%